2013
DOI: 10.1094/fg-2013-117-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Water Inputs with Subsurface Drip Irrigation May Improve Alfalfa Nutritive Value

Abstract: Irrigated alfalfa (Medicago sativa L.) is an important forage crop for western Kansas dairy producers. Concerns over decreasing groundwater supplies have prompted the need to develop more efficient methods of irrigation. We investigated the effects of a subsurface drip irrigation system at three levels of water inputs [70, 85, and 100% of plant evapotranspiration rates (ETr)] on resulting alfalfa production and nutritive value. Alfalfa was harvested at 0, 15, and 30 inches from established subsurface driplines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(18 reference statements)
1
4
0
2
Order By: Relevance
“…In general, applying the highest amount of irrigation (i.e., 610 mm during the growing season) reduced alfalfa forage nutritive values compared to other irrigation treatments. Other studies have also found that moisture stress increases alfalfa nutritive value (Vough and Marten, 1971;Snaydon, 1972;Carter and Sheaffer, 1983;Harmoney et al, 2013, Peterson et al, 1992. The results from this study suggest that any irrigation level less than full crop requirement improved forage nutritive value and suggest that more research is required on irrigation management near the full crop water requirement to determine if forage nutritive value can be improved while still maintaining full yield.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In general, applying the highest amount of irrigation (i.e., 610 mm during the growing season) reduced alfalfa forage nutritive values compared to other irrigation treatments. Other studies have also found that moisture stress increases alfalfa nutritive value (Vough and Marten, 1971;Snaydon, 1972;Carter and Sheaffer, 1983;Harmoney et al, 2013, Peterson et al, 1992. The results from this study suggest that any irrigation level less than full crop requirement improved forage nutritive value and suggest that more research is required on irrigation management near the full crop water requirement to determine if forage nutritive value can be improved while still maintaining full yield.…”
Section: Discussionsupporting
confidence: 48%
“…Many research projects have evaluated drought effects on forage yield and nutritive value in forage legumes (Gifford and Jensen, 1967;Foulds, 1978;Stroth et al, 1972;Fairbourn, 1982;Smith et al, 1986;Marten et al, 1987). Forage nutritive value in alfalfa was usually higher with water stress than without water stress (Vough and Marten, 1971;Snaydon, 1972;Carter and Sheaffer, 1983;Harmoney et al, 2013, Peterson et al, 1992. This study uniquely adds to the database of information on alfalfa nutritive value by reporting results across a complete range of ET c from fully irrigated to dryland for a complete five-year life-cycle of the crop.…”
mentioning
confidence: 99%
“…Deficit irrigation from 100ET down to 70ET did not affect alfalfa yield in Kansas (Harmoney et al, 2013), but a study in China found that the use of 60ET reduced alfalfa yield relative to 100ET (Li et al, 2016) of which yields can be influenced by timing of rainfall events or even possibly the resiliency of the crop. In our study, irrigating alfalfa at 50ET did not reduce yield which corresponds to Harmoney et al (2013). The 50ET approach increases the opportunity to capture and fully utilize rainfall, increasing the chance for efficient storage.…”
Section: Discussionmentioning
confidence: 99%
“…La alfalfa establecida con RGS bajo condiciones de estrés hídrico ha mostrado habilidad para producir mejores rendimientos que otras leguminosas forrajeras en condiciones similares (8) . Harmoney et al (9) mencionaron que aplicando láminas de riego mediante RGS con un volumen del 70 o 85 % de la evapotranspiración, no se afecta el rendimiento ni la calidad del forraje. Otros autores han encontrado que es posible someter al cultivo a estrés hídrico a partir de inicio de floración, y reducir la aplicación de agua de riego hasta un 50 % del consumo hídrico de la planta, sin afectar la producción y calidad de semilla (10) .…”
unclassified
“…Estos resultados de eficiencia de uso de agua en materia seca son similares a tratamientos de déficit hídrico, en donde la humedad del suelo fue de alrededor del 75 al 85 % de la capacidad de campo (6,23) . También con estos niveles de irrigación la alfalfa mantiene la misma proteína cruda en comparación a ensayos que mantuvieron el 100 % de humedad a capacidad de campo (9) . Con el RGS es posible maximizar la eficiencia en el uso del agua de riego, logrando obtener mayores cantidades de forraje seco y kilogramos de proteína cruda con un menor volumen de agua aplicado.…”
unclassified